Diagnóstico dos riscos e impactos ambientais da suinocultura no Ribeirão dos Pinheirinhos, município de Torrinha, (SP) - Sanabria, Jorge Mauricio [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The porcine activity is characterized by its great pollution capacity, generally produce loads of waste that usually are released in superficial water or soil without concern for the consequences to the environment. With this in mind, this study aimed to adjust the porcine production to the protection of water resources, in particular, Ribeirão dos Pinheirinhos in the town of Torrinha (SP), through inventory and diagnosis of the environmental impacts already present and environmental hazards linked to the activity in question. To achieve the proposed objectives, the productions of porcine on the studied area were raised and georeferenced, viewed and analyzed according to the technical and scientific literature. The production visited showed to be at odds with the protection of water resources due to lack of technical criteria in the development of treatment systems and waste handling, indiscriminate use of effluent and waste in the fertilization of crops and the lack of knowledge of producers on the influence of porcine waste into the environment. Based on these results, were set guidelines for action in the environmental awareness of farmers, to stimulate voluntary and conscious initiatives of environmental conservation in the direction of settlement of the activity.

A atividade suinícola caracteriza-se por sua grande capacidade poluidora, em geral produzindo cargas de efluentes que via de regra são lançados em corpos d’água ou no solo sem preocupação com as consequências ao meio ambiente. Tendo isso em vista, o presente trabalho objetivou oferecer diretrizes no sentido de compatibilizar a suinocultura à proteção dos recursos hídricos, em específico, do Ribeirão dos Pinheirinhos, no município de Torrinha (SP), através de inventário e diagnóstico dos impactos ambientais já presentes e dos riscos ambientais atrelados a atividade em questão. Para alcançar os objetivos propostos as produções suinícolas da área de estudo foram levantadas e georreferenciadas, visitadas e analisadas de acordo com bibliografia técnico-científica. As produções visitadas mostraram estar em desacordo com a proteção dos recursos hídricos, devido ausência de critério técnico na elaboração dos sistemas de tratamento e manejo dos dejetos, uso indiscriminado dos efluentes e resíduos na adubação de culturas vegetais e pelo desconhecimento dos próprios produtores sobre as influências dos dejetos no meio ambiente. Dados estes resultados foram indicadas diretrizes para atuação no âmbito da sensibilização ambiental dos produtores rurais, de modo a estimular iniciativas conscientes e voluntárias de conservação ambiental em direção a regularização da atividade.
Keywords: Geografia econômica; Impacto ambiental; Risco ambiental; Recursos hídricos; Environmental hazards; Environmental impacts; Porcine production; Water resources